2010
DOI: 10.1002/j.2050-0416.2010.tb00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Hopping Technology on the Storage-induced Appearance of Staling Aldehydes in Beer

Abstract: In this paper, the involvement of iso-α-acids in the appearance of stale flavour in beer during storage was examined. Flavour instability upon storage, by far the most important quality problem of beer, may be caused by a multitude of reactions, in particular, the degradation of trans-iso-α-acids is pivotal. In order to gain improved understanding of the beer ageing process, the behaviour of the stereoisomers of the bitter acids was studied for the first time in pilot beers at particularly high and low proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…They are formed during malt production as a result of Maillard’s reaction [ 34 ]. De Clippeleer et al [ 35 ] reported them in malt and beer samples.…”
Section: Resultsmentioning
confidence: 99%
“…They are formed during malt production as a result of Maillard’s reaction [ 34 ]. De Clippeleer et al [ 35 ] reported them in malt and beer samples.…”
Section: Resultsmentioning
confidence: 99%
“…The total heat load of the malt and thus of the future mash, wort and beer made of green malt is also significantly lower, implying a decrease in Maillard reactions and Strecker aldehyde formation. Current thinking suggests that these factors should favour an improvement in beer flavour stability ( 14–17 ) . Furthermore, higher heat loads during brewing have been associated with a decrease in free amino acid (FAN) assimilation during fermentation ( 18 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen is the primary factor influencing the shelf life of beer. Numerous changes can be ascribed to oxidation reactions, including the oxidation of higher alcohols (2), oxidative degradation of hop derived bitter acids (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and oxidation of unsaturated fatty acids (13)(14)(15). Therefore, since oxygen can initiate a wide range of chemical reactions, higher oxygen levels will significantly increase the rate of beer staling (16,17).…”
Section: Introductionmentioning
confidence: 99%